Caring for the "thinking reed". The calling of the epochs: B. Pascal and M. Heidegger - Georgiy Zaichenko, Georgiy (Sententiae, 2000)
The article examines Heidegger’s interpretation of a number of philosophical ideas, first formulated by Blaise Pascal, as the author points out. In particular, those are ideas of: 1) the relationship between man and nature as finite and infinite; 2) the disharmony of human nature; 3) the possibility of a positive resolution of the essentially antinomic contradictions between 1) and 2) only on the basis of a combination of intellectual and emotional and moral comprehension of the world. The parallelism of Pascal’s and Heidegger’s treatment of these subjects proves, in the author’s opinion, the deep affinity of these philosophies.